Bimbingan Kelompok sebagai Strategi Efektif dalam Meningkatkan Kemampuan Pemilihan Sekolah Lanjutan pada Siswa Kelas IX SMP Negeri 10 Salatiga - Taufik Bowo Nurjati Taufik; Adinda Maya Kumala; Suldi Mugi Prayitno; Via Dewi Harya Ningtyas; Noor Malihah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aimed to determine the effectiveness of group guidance services in improving the ability of ninth-grade students at SMP Negeri 10 Salatiga to choose further education schools. The background of this study was based on the low ability of some students to make independent and rational decisions regarding further school selection, as indicated by their tendency to follow peers’ choices or external influences without considering their interests, talents, and personal potential. This study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of an experimental group and a control group selected through purposive sampling techniques. Data were collected through questionnaires on students’ ability to choose further education schools, observations, interviews, and documentation. The data were analyzed using an independent sample t-test and N-Gain analysis to determine the effectiveness of the service. The results showed that group guidance services were effective in improving students’ ability to select further education schools. This was evidenced by a significant difference between the experimental and control groups in the posttest results, as well as a higher N-Gain score in the experimental group. Group guidance services helped students improve their understanding of information related to further education schools, identify their interests and personal potential, and develop more rational educational decision-making skills. The effectiveness of the service was influenced by group dynamics, peer discussions, and self-exploration processes that developed through interactions among group members. Therefore, group guidance services can serve as an effective strategy to help junior high school students make independent, well-directed, and appropriate decisions regarding further education choices based on their interests and potential.